Ventral Windowed Total Contact Casts Safely Offload Diabetic Feet and Allow Access to the Foot. (January 2022) - Hochlenert, Dirk; Fischer, Claudia
Background: Irremovable total contact casts (TCCs) are the gold standard to offload diabetic foot ulcers (DFUs) and to immobilize feet with active Charcot neuro-osteoarthropathy (CN). They do not allow checks of the foot and are contraindicated in people with peripheral arterial disease (PAD). Frequently, removable TCCs and other removable devices are used because they allow wound care, modifications of the inner surface of the cast, and checks of the foot. The authors propose TCCs with ventral windows (VW-TCCs) whenever patients with high-risk conditions show poor adherence to wearing a removable cast all the time and access to the foot is necessary. Methods: This retrospective study compares treatments with bivalved, removable TCCs applied prior to the introduction of the novel design (from 1 January 2016 to 1 July 2017, " c ") to treatments in the following period ( t ) with both bivalved removable TCCs and VW-TCCs in use. Results: Forty-five treatments after introduction (17 with the VW-TCC) showed a 52.8% lower median time to reach remission of the DFS than 41 controls (128/267 days, log-rank test P  = .013). Reasons given for not using the novel design were: sufficient offloading with a removable TCC (16), patient preference (six), anatomical conditions (two), casts applied as a service for other facilities (three), and calf ulcers (one). Adverse effects from both designs were uncommon and not severe. Conclusions: VW-TCCs combine advantages of both removable and irremovable TCCs. Complications do not limit the use, even in patients with PAD.